Bisphenol A attenuates testosterone synthesis via increasing apolipoprotein A1-mediated reverse cholesterol transport in mice - Zhao, Tong; Yang, Wenzhe; Pan, Feilong; Wang, Jinhao; Shao, Wenqi; Chen, Fangfang; Liu, Kexiang; Zhao, Shuchen; Zhao, Lijia (Frontiers in Endocrinology, 2025)
Bisphenol A (BPA), a widely used chemical compound in plastic manufacturing, has become ubiquitous in the environment. Previous studies have highlighted its adverse effects on reproductive function, as BPA exposure reduces testosterone levels. Cholesterol is involved in testosterone synthesis in Leydig cells. However, research on the mechanisms by which BPA affects testosterone synthesis from the perspective of reverse cholesterol transport (RCT) remains limited. This study aimed to investigate the effects of BPA on cholesterol levels, lipid droplet accumulation, and testosterone synthesis in TM3 cells and mice via Apolipoprotein A1 (APOA1)-mediated RCT. Adult male mice were treated by intraperitoneal injection of corn oil containing BPA (20 mg/kg) for 7 days. Testes were collected for protein extraction, RNA extraction, Oil red O staining or for Biochemical analysis. Serums were collected for detection of testosterone levels. flow cytometry, CCK8 assay, immunofluorescence or Filipin III staining was used to detect the effect of BPA on the TM3 cells. It was observed that serum and testicular testosterone levels were drastically reduced in BPA-treated mice. Moreover, lipid droplets accumulation and testicular total (TC) and free cholesterol (FC) levels were reduced in the mouse testes. Conversely, testicular high-density lipoprotein (HDL) content was partially elevated. Furthermore, BPA markedly enhanced Apoa1 mRNA and protein expression in the mouse model. Notably, BPA significantly upregulated Apoa1 mRNA and protein level, reduced cholesterol levels and lipid droplets accumulation, and attenuated testosterone synthesis in TM3 cells. In addition, exogenous supplement with 22-hydoxycholesterol promoted testosterone synthesis and alleviated the inhibitory effect of BPA on testosterone synthesis. Taken together, these results suggest that BPA upregulates APOA1 expression, enhances RCT, and ultimately reduces TC and FC levels in the testis. This cholesterol reduction likely led to testosterone synthesis disorders in the model, indicating that BPA inhibits testosterone synthesis in mice by disrupting cholesterol transport.